Faktor Pengaruh Abcd Terhadap Keputusan Pembelian Asuransi Prulink Prudential - Bobby Kurniawan (Universitas Tarumanagara, 2019)
The development life insurance company in Indonesia has grown from year to year. In line with the growth of this industry, competition among life insurance companies also increased. As life insurance companies, Prudential need a strategy to achieve the goals which have been determined. Prudential need to know the behavior patterns of consumer when they make decisions to purchase product. This research aims to study the extent to which implementation strategies can influence buying decision of Prulink Term. This research employ descriptive correlation method. In this research descriptive approach is used to give overview of related strategies like marketing communication, product knowledge, survey undertaken by Prudential. Where the correlation approach is used to determine how big the customer purchasing decision.Independent variable of this study is that strategies are divided into several independent variables, among others, advertisement, sales promotion, direct and interactive marketing, personal sales. Whereas for the dependent variable of this study is the consumer purchasing decision of Prulink Term insurance product.